IMPLEMENTATION OF THE CSR PROGRAM BASED ON TRI HITA KARANA - Budanti, Ni Putu Lion; Rustiarini, Ni Wayan (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
AbstractThe accounting field has transformed to achieve economic performance without ignoring social and environmental aspects. One form of implementing social accounting is the practice of Corporate Social Responsibility. Implementing CSR in Bali is closely related to Balinese culture called Tri Hita Karana. The purpose of this research is to determine the implementation of company CSR programs in Bali which are based on Tri Hita Karana. This qualitative study uses a case study method on the Social Project Bali. Social Project Bali is a non-profit organization that operates in education, environment, and social humanity. Data collection uses the interview method. The results of the interviews revealed that the role of the non-profit organization Social Project Bali in implementing corporate CSR programs in Bali is enormous. The implementation of the CSR program in this organization focuses on three main areas: education, environment, and social humanity. The implementation of this CSR program is based on local Balinese wisdom, namely Tri Hita Karana. The distribution of this CSR program also received a positive response from the community so that it could meet community needs. Companies are expected to increase their participation in CSR programs, especially in the environmental sector.Keywords: Corporate Social Responsibility; Tri Hita Karana; Non-profit organization AbstrakBidang akuntansi telah bertransformasi untuk mencapai kinerja ekonomi tanpa mengabaikan aspek sosial dan lingkungan. Salah satu bentuk penerapan akuntansi sosial adalah praktik Corporate Social Responsibility. Pelaksanaan CSR di Bali sangat erat kaitannya dengan budaya Bali yang disebut dengan Tri Hita Karana. Tujuan dari penelitian ini adalah untuk mengetahui implementasi program CSR perusahaan di Bali yang berlandaskan Tri Hita Karana. Penelitian kualitatif ini menggunakan metode studi kasus pada Social Project Bali. Social Project Bali merupakan organisasi nirlaba yang bergerak di bidang pendidikan, lingkungan, dan sosial kemanusiaan. Pengumpulan data menggunakan metode wawancara. Hasil wawancara mengungkapkan bahwa peran organisasi nirlaba Social Project Bali dalam mengimplementasikan program CSR perusahaan di Bali sangat besar. Pelaksanaan program CSR pada organisasi ini berfokus pada tiga bidang utama yaitu pendidikan, lingkungan, dan sosial kemanusiaan. Pelaksanaan program CSR ini berlandaskan pada kearifan lokal Bali, yaitu Tri Hita Karana. Penyaluran program CSR ini juga mendapat respon positif dari masyarakat sehingga dapat memenuhi kebutuhan masyarakat. Perusahaan diharapkan dapat meningkatkan partisipasinya dalam program CSR khususnya di bidang lingkungan.Kata kunci: Tanggung Jawab Sosial Perusahaan; Tri Hita Karana; Organisasi nirlaba